Effects of Human Papillomavirus Infection on Semen Quality: a Meta-analysis - Caixia LI, Yun DENG, Juan DU, Yanru ZHANG, Wenyi GAO (Zhongguo quanke yixue, 2022)
Background Human papillomavirus (HPV) has been considered as one of the most common sexually transmitted viruses that may be linked to unexplained infertility in men. Current studies have indicated that HPV infection is partly associated with sperm quality in men, but have not shown consistent results. Objective To assess the possible influence of HPV infection on semen quality in men. Methods Studies examining the association between HPV infection and semen quality in men published from January 2000 to October 2021 were searched in databases of PubMed, EMBase and Cochrane Library. Literature enrollment, data extraction, and methodological quality assessment were performed. RevMan 5.3 was used for meta-analysis. Results Seven studies were identified, including 2 236 cases in total, and 331 of them were positive for HPV DNA, and the other 1 905 were negative. All these studies adopted an observational design, and were rated as having a moderate to severe risk of bias. Analysis revealed that compared to the controls, the HPV-infected semen samples showed lower sperm motility and lower rate of normal morphology〔MD=-8.29, 95%CI (-10.03, -6.55), P<0.000 01; MD=-3.75, 95%CI (-5.58, -1.92), P<0.000 1〕, but demonstrated insignificantly differences in sperm concentration, sperm volume and sperm count〔MD=-4.08, 95%CI (-10.29, 2.13), P=0.20; MD=-0.13, 95%CI (-0.25, 0), P=0.05; MD=-12.44, 95%CI (-37.30, 12.43), P=0.33〕. Conclusion HPV infection may be associated with decreased sperm motility and normal morphology rate.